Prevalence of Hepatitis E Virus in Populations of Wild Animals in Comparison with Animals Bred in Game Enclosures - Kubankova, Monika; Kralik, Petr; Lamka, Jiri; Zakovcik, Vladimir; Dolanský, Marek; Vasickova, Petra (Food and environmental virology, 2015)
Hepatitis E virus (HEV) is now accepted as a zoonotic virus, and domestic pigs, wild boars and deer are recognised as natural reservoirs of the pathogen. In this study, 762 animals (wild boars, fallow deer, red deer, sika deer, roe deer and mouflons) originating from the wild and from game enclosures were tested for the presence of HEV RNA by qRT-PCR. HEV RNA was detected in wild boars (96/450), red deer (2/169), roe deer (1/30) and mouflons (5/39). The sequence relationship between HEV isolates from wild boars and domestic pigs or humans indicate a circulation of HEV in the Czech Republic.